Notes on the inherent powers of international organizations - Gadkowski, Andrzej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The aim of this article is to present the main aspects of the concept of the inherent powers of international organizations. This is a topic of importance, yet it is often overlooked in the existing literature, which predominantly delves into attributed powers and implied powers of international organizations. The author discusses the essence of Finn Seyersted’s concept of inherent powers and the doctrinal assessment of this concept. The author also presents the assessment of the concept of inherent powers made by legal scholars – their nuanced interpretations and acceptance – shedding light on the varying viewpoints on this concept.